Multidrug-Resistant Bacterial Colonization and Infections in Large Retrospective Cohort of Mechanically Ventilated COVID-19 Patients - Davide Mangioni; Liliane Chatenoud; Jacopo Colombo; Emanuele Palomba; Fernando A. Guerrero; Matteo Bolis; Nicola Bottino; Giuseppe Breda; Maria V. Chiaruttini; Gabriele Fior; Manuela Marotta; Giovanni Massobrio; et al. (Emerging Infectious Diseases, 2023)
Few data are available on incidence of multidrug-resistant organism (MDRO) colonization and infections in mechanically ventilated patients, particularly during the COVID-19 pandemic. We retrospectively evaluated all patients admitted to the COVID-19 intensive care unit (ICU) of Hub Hospital in Milan, Italy, during October 2020‒May 2021. Microbiologic surveillance was standardized with active screening at admission and weekly during ICU stay. Of 435 patients, 88 (20.2%) had MDROs isolated ≤48 h after admission. Of the remaining patients, MDRO colonization was diagnosed in 173 (51.2%), MDRO infections in 95 (28.1%), and non-MDRO infections in 212 (62.7%). Non-MDRO infections occurred earlier than MDRO infections (6 days vs. 10 days; p<0.001). Previous exposure to antimicrobial drugs within the ICU was higher in MDRO patients than in non-MDRO patients (116/197 [58.9%] vs. 18/140 [12.9%]; p<0.001). Our findings might serve as warnings for future respiratory viral pandemics and call for increased measures of antimicrobial stewardship and infection control.